A rare case of rectal adenocarcinoma and small-bowel neuroendocrine tumor in a young patient with long-standing Crohn's disease: A case report - Nahla Azzam (Wolters Kluwer Medknow Publications, 2021)
Background: The association of adenocarcinoma of the colon and neuroendocrine tumor (NET) of the small bowel has been previously described in Crohn's disease (CD), however the concomitance of both neoplasms is extremely rare. Here, the author reports a rare case of both rectal adenocarcinoma and small-bowel NET in a young male with long-standing CD. Case Report: The patient presented with clinical and radiological features of intestinal obstruction 2 years posttotal colectomy and end ileostomy for rectal cancer and found to have ileal NET. Conclusion: Small-bowel NET symptoms can mimic CD and is a rare entity, but physicians should suspect NETs in CD patients presenting with intestinal obstruction.